Inestabilidad cariológica durante la formación de células madres del polen en Aloe vera(Aloaceae) - Imery Buiza, José (2007)
In order to clarify possible cytogenetic anomalies that reduce pollen fertility, premeiotic mitosis was studied in Aloe vera plants from a naturalized population in the northeast of Venezuela (10°34’15’’ N and 64°12’08’’ W). Karyological configurations were evaluated during the stage of cell proliferation leading to the formation of pollen mother cells (PMCs). The sampling was carried out in March 2005, choosing inflorescences without mechanical or biological damage from 25 plants selected at random. Flower buds (FB) 2 to 6 mm in length were collected from 7:00 AM through 6:00 PM, their perianths removed, and fixed in Carnoy I (3:1 ethanol/glacial acetic acid) for 24 h and stored in ethanol (70 % v/v) until observation. Light microscope observations were done on temporary preparations obtained by overflowing anther content suspended in acetic orcein (1.5 % w/v) for 5 min and softly squashing with the cover slip. A total of 9 411 cells were analyzed. Upper mitotic activity was observed in FB from 3.8 ± 0.09 mm long, collected at 11:00 AM through 1:00 PM; 17% of PMCs showed one to eight sister chromatid bridges from anaphase to telophase; 13%, one to seven micronucleus of variable diameter (0.9 to 4.8 μm); 8.1% were united by thin chromatin filaments, and 0.1% lacked a nucleus. Other evaluated cells (61.8%) had apparently normal mitotic configurations, without considerable morphometric variations. The evident irregular proliferation of a PMCs fraction (39.2%) suggests that environmental stress conditions (day temperatures ranging 32.7 to 39.8ºC, high solar radiation and low humidity) induce chromosome instability and physiologic changes that affect the normal development during premeiotic mitosis. As a consequence, loss or addition of chromosome fragments can occur in association with deficiencies and gene duplications.